Preparation and Physico Chemical Analysis of Arka Lavan (International Journal of Ayurveda and Pharma Research, 2023)
Lavana kalpanas are prepared by using predominantly Lavanas and herbs with Putagni samskara. Arka lavana is a herbo mineral preparation mentioned in Rasa Tarangini, Bhaishajya Ratnavali etc. It is indicated for Yakrit Pleeha Rogas along with water or butter milk as Anupana. The ingredients of this preparation are Arka patra (leaves of Calotropis procera) and Saindhava lavana (rock salt) in equal parts. Standardization is an essential part for proving therapeutic efficacy of a preparation. In this study Arka lavana has prepared according to the traditional method mentioned in textual reference from Rasa Tarangini ie; by Puta Paka method. The analytical study of this preparation was carried out including organoleptic and physicochemical parameters. The pharmaceutical procedure as well as Analytical results can be considered as a reference for further studies.